The study of the antinutritional threshold of glycinin in piglets: impact on growth performance, nutrient digestion, allergic reactions, intestinal permeability and morphology - Liu, Ning; Fu, Xueliang; Zhang, Bolin; Zhong, Qingzhen; Bao, Nan; Sun, Zewei (Frontiers in Veterinary Science, 2025)
Glycinin is identified as one of the major dietary allergens in soybean. However, the safety threshold of glycinin in piglets have not been clearly understood. The purpose of this study was to investigate the anti-nutritional effects and sensitization threshold of purified glycinin in weaned piglets. In this experiment, 45 21-day-old weaned castrated piglets (Duroc × Landrace × Yorkshire), with a similar initial body weight of 9.95 ± 0.43 kg, were randomly divided into five groups with nine replicates per group. The piglets in the control group were fed a basal diet, while the piglets in the experimental groups were fed diets containing 1, 2, 3 and 4% purified glycinin, respectively, based on the same basal diet. After determination, the glycine content in the diets of each group was 0.704, 8.779, 16.857, 24.934, and 33.011 mg/g, respectively. Samples of feces, serum, digesta, as well as the segments and mucosa of the small intestine, were collected. The measured parameters included the nutrient apparent metabolic rate, digestive enzyme activities, levels of specific immunoglobulin G, histamine (HIS), and D-lactic acid (D-LA) levels, along with small intestinal morphology. The results showed that, compared to the control group, the average daily gain, the average daily feed intake, and the ratio of weight gain to feed intake of the piglets were linearly and quadratically decreased by the inclusion of 2, 3, and 4% glycinin in the diets (p < 0.05). In addition, positive skin sensitization, increased erythema diameter, and elevated specific immunoglobulin G titers were induced by glycinin inclusion (p < 0.05). In addition, 2, 3, and 4% glycinin administration led to decreases in the apparent nutrient metabolic ratio and digestive enzyme activities (p < 0.05). Moreover, the levels of HIS, diamine oxidase, and D-lactic acid in the small intestine were increased in response to 3 and 4% glycinin supplementation (p < 0.05). In addition, the reduced D-xylose concentration and damaged intestinal morphology in the piglets observed were induced by the inclusion of 2, 3, and 4% glycinin (p < 0.05). The above results indicate that glycinin inclusion at doses above 1% can trigger allergenic effects, including increased erythema diameter, elevated specific immunoglobulin G titers, and higher levels of HIS and D-lactic acid. In contrast, glycinin inclusion at doses above 2% can induce some anti-nutrition effects, such as decreased apparent nutrient metabolic ratio, reduced digestive enzyme activities, and damaged small intestinal morphology. In addition, the information mentioned above implied that the sensitization threshold of glycinin administration in the piglets was 8.779 mg/g and the anti-nutrition threshold was 16.857 mg/g.